The Reduction of Child Mortality in the Middle East and North Africa : A Success Story - Iqbal, Farrukh; Kiendrebeogo, Youssouf (World Bank Group, Washington, DC, 2014)
Although child mortality rates have declined all across the developing world over the past 40 years, they have declined the most in the Middle East and North Africa region. This paper documents this remarkable experience and shows that it is broad based in the sense that all countries in the Middle East and North Africa experienced significant declines in child mortality over this period and each country did better than most of its comparators. In looking for the sources of the region s performance edge, the paper confirms the importance of such determinants of child mortality as income growth, education stock, public spending on health, urbanization, and food sufficiency. In addition, the paper establishes that the initial level of mortality has a substantial influence on the pace of subsequent child mortality decline. Of these factors, food sufficiency status is found to contribute to the region s performance edge over all developing regions, while the other factors are found to matter to varying degrees in selected pairwise regional comparisons.